New estimates considering the generalized proportional Hadamard fractional integral operators - Zhou, Shuang-Shuang; Rashid, Saima; Jarad, Fahd; Kalsoom, Humaira; Chu, Yu-Ming (Advances in difference equations, 2020)
In the article, we describe the Grüss type inequality, provide some related inequalities by use of suitable fractional integral operators, address several variants by utilizing the generalized proportional Hadamard fractional (GPHF) integral operator. It is pointed out that our introduced new integral operators with nonlocal kernel have diversified applications. Our obtained results show the computed outcomes for an exceptional choice to the GPHF integral operator with parameter and the proportionality index. Additionally, we illustrate two examples that can numerically approximate these operators.